2019
DOI: 10.15666/aeer/1706_1285912868
|View full text |Cite
|
Sign up to set email alerts
|

Varitation of Stomatal Characteristics in Broad Leaved Species Based on Habitat

Abstract: This research aims to find the habitat-dependent variation of micromorphological characteristics in the leaves of Fraxinus excelsior (European ash), Platanus orientalis (Plane tree) and Tilia tomentosa (Silver lime) collected from 6 different cities of different climates. The leaves were collected in Turkey in the cities of Rize, Samsun, İzmir, Antalya, Sivas, and Ankara. Samsun and Rize fall under the Black Sea climate region, Ankara and Sivas under the continental climate, whereas Antalya and İzmir enjoy a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Thus, the linear change in Ni concentration by the traffic volume and the lower level of relationship between Co concentration change and traffic volume can be considered as a result of elements, plant structure, and interaction between them because many factors affect the intake and accumulation of heavy metals in plants. Besides the factors related to plant structure and environments such as plant species, precipitation, moist level, plant habitus, and organ structure, the type of heavy metal and its interaction with the plant are also important factors affecting the heavy metal accumulation in the organs of the plant (Cetin et al 2018a(Cetin et al , 2018bYigit et al 2019;Aricak et al 2020;Sevik et al 2020c).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the linear change in Ni concentration by the traffic volume and the lower level of relationship between Co concentration change and traffic volume can be considered as a result of elements, plant structure, and interaction between them because many factors affect the intake and accumulation of heavy metals in plants. Besides the factors related to plant structure and environments such as plant species, precipitation, moist level, plant habitus, and organ structure, the type of heavy metal and its interaction with the plant are also important factors affecting the heavy metal accumulation in the organs of the plant (Cetin et al 2018a(Cetin et al , 2018bYigit et al 2019;Aricak et al 2020;Sevik et al 2020c).…”
Section: Resultsmentioning
confidence: 99%
“…The scanning electron microscope, which was used in taking the stoma images within the scope of the present study, provides a high level of magnification thanks to high-resolution imaging techniques. For this reason, it is possible to obtain morphological, structural, and elemental data from the plants at a high zoom level [9,24]. The data obtained can be used in various areas such as determining the stress level of plants, genetic variation studies, and determining the most suitable plant growth conditions [8].…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, it is known that genetic variations may be seen within the same species due to differences in growing conditions and origins [31][32][33]. Previous studies reported that stomatal characteristics might significantly vary between the individuals, which have been grown in the same environment, from the same species [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors such as precipitation, temperature, stress factors, light, air pollution, and soil structure which affect the morphological characteristics and development of plants (Cetin et al, 2018a,b;Aricak et al, 2020). In addition to ecological conditions, the studies conducted reveal that the factors such as pruning, hormone applications, spraying, shading, and fertilizing factors are also effective on plant morphological characteristics and development (Guney et al, 2016;Sevik and Cetin, 2016;Yigit et al, 2019). However, the reactions given to these conditions by plants are also shaped under the influence of genetic structure.…”
Section: Species Performance In the Arid Environmentmentioning
confidence: 99%